Pengaruh Mekanisme Tata Kelola Perusahaan terhadap Kinerja Keuangan Perusahaan: Studi Empiris pada Perusahaan Non Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Utama, Bryan Pramudya; Sastrodiharjo, Istianingsih; Mukti, Aloysius Harry (Penerbit Goodwood, 2023)
Purpose: This study examines the effects of corporate governance mechanisms on financial performance. The population in this study is all consumer non-cyclical companies listed on the Indonesia Stock Exchange in 2019-2021). Methodology/approach: The variables used in this study were the company's financial performance as the dependent variable, the Influence of Corporate Governance Mechanisms as independent variables, and the Audit Committee and independent Board of Commissioners as control variables. The sampling technique used was the purposive sampling method and 126 data samples were obtained. The analytical method used is Descriptive Statistical Analysis, Classical Assumption Test, Correlation Test, Multiple Linear Regression Test, and Hypothesis Test Results: The results show that the influence of the Corporate Governance Mechanism with the Proxy of the Audit Committee has no effect on financial performance. The Independent Board of Commissioners has a positive effect on financial performance. In addition to the control variable, Firm Size does not affect financial performance, and Board Size does not affect financial performance.